An Account of the First Settlement, Laws, Form of Government, and Police, of the Cessares, a People of South America: In Nine Letters, from Mr. Vander Neck [pseud.], one of the Senators of that Nation, to his Friend in Holland. With Notes by the Editor - [James] [Burgh] (1714-75) (Ptd. for J. Payne, 1764)
A detailed, regimented eutopia presented in the founding of a colony. Each male colonist to get sufficient land for their needs and the rest reserved for their descendants. Everyone is expected to be "sober, industrious and peaceable" (Claeys 80), and anything that would lead to a different condition is illegal. There are no lawyers, and plain speaking in trials is expected. Inspectors report annually on both the condition of the people, with ministers a particular concern, and that of the infrastructure. Useful trades taught along with intellectual, moral, and religious material.
Rpt. in Utopias of the British Enlightenment. Ed. Gregory Claeys (Cambridge, Eng.: Cambridge University Press, 1994), 71-136.
Keywords: English author; Scottish author